PERANCANGAN SISTEM INFORMASI E-LOGISTIC STUDI KASUS : PT KAMADJAJA LOGISTIC - Denny Rianditha AP; Risma Anggraini (Fakultas Ilmu Komputer dan Desain - Unsurya, 2022)
The magnitude of the influence of technology in a company on data processing, one of which is PT Kamadjaja Logistics which is a company engaged in the service of shipping containers to all regions of Indonesia and the process of recording container data used at PT Kamadjaja Logistics is still done manually, starting from inputting Customer data until the input of container data that has been delivered to the regional recipient so that it is possible during the process of an error to record, inaccurate reports made and delays and the length of time in the search for the required data. The customer is one of the top priorities that must be served well. In this case, almost all customers of PT Kamadjaja Logistics want to get quality services, precisely and quickly as well as in accordance with the estimation of arriving in the area. Customers want containers to arrive on schedule or even fasterÂ Keywords: Information System Design, Kontainer, PT Kamadjaja Logistic, Data Processing